Conditions and determinants of internationalization of Colombian industrial companies: a quantitative approach at the level of the firm - Peñaloza, Héctor Alberto Botello; Rincón, Isaac Guerrero (Universidad Pedagógica y Tecnológica de Colombia, 2014)
In the last ten years has seen a boost by Colombian companies in offering their products in international markets in coordination with the other countries of Latin America. In this sense, the objective of this work is to explore quantitatively the conditions and determinants that have allowed this international expansion of Colombian industrial firms between 2006 and 2010. For methodological purposes is used a logit model on a sample of 10,000 companies. Estimates show that specific assets such as technological capability and characteristics by sector are the factors that have had the greatest influence on export performance in the years of study